Sarilaysay tinig ng 20 babae sa sariling danas bilang manunulat - Yu, Rosario Torres- (Manila Inilathala at ipinamamahagi ng Anvil Pub., 2000)
Accounts of 20 Philippines women writers on their experience as writers.
Includes bibliographical references (p. 337-338).
In Tagalog.
Keywords: Women authors, Filipino; Women and literature -- Philippines; Philippine literature -- Women authors -- History and criticism